Development Of Plate & Forging Work Instructions As Practicum Guidelines in the Department of Mechanical Engineering - Pratama, Hendra Saputra; Hartanto, Anton (Jurnal Basicedu, 2023)
Education is a complex process, various problems in the learning process need to be aligned and strengthened in order to create appropriate learning conditions, so that optimal learning results are obtained. To complete the learning and learning components in tertiary institutions, especially in the Plat & Forging practicum course, the Department of Mechanical Engineering, State University of Surabaya, it is necessary to have media or tools that are able to stimulate learning effectively and efficiently, one of which is by utilizing work instructions as a guide, especially in subjects practicum based courses. This research uses the development method. The development model used is a procedural model, namely a descriptive model that shows the steps that must be taken to produce a product. Sources of data were obtained from literature sources of work instructions in the Plate & Forging practicum course that had been used, the data collection technique used the questionnaire method with a sample of students who were or had taken the Plate & Forging Practice course. Overall, the average score of students who use the development of work instruction teaching materials is 3.38 out of a range of 4, which is in the very feasible and usable category. With this work instruction, it is hoped that the practitioner will be able to translate from the form of images and writings to become a workpiece, so that independence is achieved in the Plate & Forging practicum activities